Character Values Analysis in the English Textbook for High School Students in Ambon: Bahasa Inggris Fase E SMA - Mahulette, Astrid (MATAI: International Journal of Language Education, 2025)
This study examined the category of character values, the integration of character values, and the strategies of delivering character values in the English textbook for grade tenth entitled Bahasa Inggris Fase E SMA. This research employed content analysis method. The finding showed that (1) Character values in English language textbook comprises five characters categories, the value of human character in relation to the almighty God, oneself, others, the environment, and the nation. The five categories of character values are not spread out evenly in each unit in the textbook. But this is not being a problem since there are other values which could be fulfilled by other tasks in each unit. (2) The five categories of character value were integrated into four components of language, i.e., listening, speaking, reading, and writing. The integration of character values in the textbook are spread evenly in each skill. (3) the strategies of delivering character values in the textbook consists of two forms, i.e., implicit and explicit forms. The explicit form is more dominant than implicit. To test the validity of the data, the semantic validity and reliability (intra-rater and inter-rater) were used. This implies that in writing the textbook, the writers take account of the cognitive aspect and students’ psychological development. Therefore, this textbook is suitable as the materials and guidance for English teachers to teach English and to develop the character education values suggested by the Merdeka Curriculum to the students. Keywords: content analysis, cognitive aspect, psychological development